An Overview on Gelatin-Based Biofilm for Chronic Diabetic Wound Healing - Selimin, Mohamad Ali; Chuan, Lee Te (Trends in Immunotherapy, 2025)
Millions of people worldwide suffer from diabetes, and many develop chronic wounds like diabetic foot ulcers that struggle to heal. Traditional wound dressings often fall short. They cannot effectively control infections or create the ideal conditions for healing. This is where gelatin-based biofilms come in. Made from collagen, gelatin is naturally compatible with the human body and can be tailored to meet the specific needs of diabetic wounds. This overview explores how gelatin-based biofilms are revolutionising wound care. Recent advances in gelatin-based biomaterials demonstrate significant promise for improving wound healing outcomes. Studies show these materials achieve 50–100% wound closure within 12–18 days, with gelatin-QAS/PCL/bioglass nanofibers and GelMA/graphene oxide composites showing remarkably rapid healing. The materials exhibit strong antibacterial properties against common pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA)and E. coli, while maintaining excellent cell viability above 80%. Mechanical testing reveals favourable properties, including compressive strength of up to 412 kPa and porous structures that are ideal for tissue regeneration. Key findings include enhanced granulation tissue formation (reaching a thickness of 1.6 mm), reduced wound areas (remaining at just 4.9% after treatment), and promotion of neurovascular regeneration. The evidence suggests gelatin-based biomaterials are ready for more extensive clinical validation, with future research needed to optimise degradation rates and transition these promising results into clinical practice. They are paving the way for real-world solutions that could transform the lives of people with diabetes. By combining nature’s building blocks with cutting-edge science, these advanced dressings offer hope for faster, safer, and more effective wound healing.